Signs and symptoms associated with digestive tract development - Mauro Batista de Morais (Brazilian Society of Pediatrics, 2016)
Objective: To analyze the development and prevalence of gastrointestinal signs and symptoms associated with the development of the digestive tract, and to assess the measures aimed to reduce their negative impacts. Source of data: Considering the scope and comprehensiveness of the subject, a systematic review of the literature was not carried out. The Medline database was used to identify references that would allow the analysis of the study topics. Synthesis of results: Infants frequently show several gastrointestinal signs and symptoms. These clinical manifestations can be part of gastrointestinal functional disorders such as infantile colic, infant regurgitation, and functional constipation. Allergy to cow's milk protein and gastroesophageal reflux disease are also causes of these clinical manifestations and represent an important and difficult differential diagnosis. The diseases that course with gastrointestinal signs and symptoms can have an impact on family dynamics and maternal emotional status, and may be associated with future problems in the child's life. Comprehensive pediatric care is essential for diagnosis and treatment. Maternal breastfeeding should always be maintained. Some special formulas can contribute to the control of clinical manifestations depending on the established diagnosis. Conclusion: During the normal development of the digestive tract, several gastrointestinal signs and symptoms may occur, usually resulting from functional gastrointestinal disorders, gastroesophageal reflux disease, and allergy to cow's milk protein. Breastfeeding should always be maintained.